El surgimiento de "lo económico": Acción y orden social dentro de la tradición económica - Loyola Campos, Javier (Revista de Sociología, 2011)
The article analyses and gives account of the process of constitution of economic field as an independent domain, endowed with an inner coherence of its own, which permits the delimitation of a particular object of study and consequently the emergence of a specific discipline to deal with it: economic science. This process is important to sociology as long as it allows tracking the origin of the solution that traditional economics gives to one of the main problems of sociology, namely, the link between social action and economic order. The paper addresses the independence of economic domain following and broadening the three-author scheme proposed by Dumont (1999), with special attention to the progressive configuration of a particular notion of human action –the homo oeconomicus– and a specific concept of social order in close relation to it –a spontaneous order based on mutual benefits–.